På sporet af det hellige: Om Mircea Eliades hierologi - Jensen, Tim; Rothstein, Mikael (Psyke & Logos, 2023)
This paper: On The Track of the Sacred - On Mircea Eliade’s Hierology, presents the basic theories about the Holy or the Sacred, as developed by the phenomenologist of religion Mircea Eliade (1907-1986). Further the authors briefly discuss (among other things) wether the Holy, in Eliades understanding, has an actual existance or wether it is a product of human, religious creativity, i.e. a psychological phenomenon of some kind. One theme in particular is taken into consideration, namely Eliades notion that states that the Holy manifests itself through the profane. According to Eliade, the phenomenon throught which the Holy manifests itself is not Holy. It remains in its essence profane. The incarnation of God in Jesus Christ, as an example, is regarded as a supreme expression of the manifestation of the Holy (God) through the otherwise profane (Jesus/Man). Through an example derived from the vaisnava-tradition of Hinduism, it is shown however, that things or phenomenons in themselves can be Holy. The example here indicate the holyness of Nature in vaisnava heology, through references to Bhagavad-gita and Bhagavad Purana. (Srimad Bhagavatam) (including commentaries by followers of this religion). In these texts it is stated, that God (Krishna) manifests himself in every atom of Creation, that Nature is His body, and that the forces of Nature (the gunas) are within him. Krishna does not merely manifests Himself throught the natura) objects: He is so deeple identified with Nature, that any separate identification of Nature as a category, apart from Krishna is meeningless. Thus the paper indicates a problem in Eliades universally applied hierology, as the Holy in vaisnava tradition is identical with the objects in which it manifests. The authors wishes to emphazise that the paper is an introduction or a scetch with no fullscale argumentation.